"I Want That": Human-in-the-Loop Control of a Wheelchair-Mounted Robotic Arm. Issue 1 (2nd May 2011) - Tsui, Katherine M.; Kim, Dae-Jin; Behal, Aman; Kontak, David; Yanco, Holly A.
Abstract : Wheelchair-mounted robotic arms have been commercially available for a decade. In order to operate these robotic arms, a user must have a high level of cognitive function. Our research focuses on replacing a manufacturer-provided, menu-based interface with a vision-based system while adding autonomy to reduce the cognitive load. Instead of manual task decomposition and execution, the user explicitly designates the end goal, and the system autonomously retrieves the object. In this paper, we present the complete system which can autonomously retrieve a desired object from a shelf. We also present the results of a 15-week study in which 12 participants from our target population used our system, totaling 198 trials.